Writing Islam in India: K. A. Nizami’s Historiographical Contribution to Islamic Studies - Nasir Ahmad Ganai (al-Wadhih: Journal of Islamic History and Civilization, 2025)
This paper looks at the historical contributions of Khaliq Ahmad Nizami, one of the most significant Indian Muslim scholars of the twentieth century. His writings on Indo-Islamic history, especially Sufism and Muslim political institutions, are essential in Islamic studies. By examining Nizami’s important texts, this study explores how his way of writing Islamic history combines ethical, spiritual, and interpretive aspects. These aspects challenge the prevailing secular or orientalist views often found in postcolonial South Asian history. The paper argues that Nizami’s approach does more than just record events. It seeks to recover the moral and intellectual energy of Islamic traditions through careful readings of Persian sources, biographies, and political stories. Using a qualitative, interpretive method, the research emphasizes Nizami’s focus on Sufi ideals like ikhlāṣ (sincerity) and adab (moral behavior) as significant historical forces. This highlights the ethical actions of Muslim individuals in medieval India. While recognizing the limits of his focus and geographical range, the study confirms that Nizami’s ideas remain important for today’s discussions in Islamic history. It wraps up with suggestions for future research that could expand on Nizami’s work, creating more spiritually sensitive and ethically based stories about Islamic history.